The Mokopane college through the years, 1940's - 1990's - Bhyat, Faizul (My University, 2016)
This thesis concerns itself with resistance during tho decade of tho 80s. Much of the literature has focussed on student resistance. There has in general been very little that has examined resistance of student teachers, Student teachers are-vital change agents in education for the futuro. If there is to be any Intervention in teacher training colleges, then there needs to be an understanding of historical power relations and the f0n11S of'resistance in these institutions. The aim of the research report is to dccumer.t and explain why and how student teachers at the Mokopane College of Education become politically militant during the decade of the 80s. The contention is tha: under extremely repressive and authoritarian conditions such as those faced by student teachers in homeland lnstitutloue, resistance can take many forms. However, as the study concludes. it became general and militant in this instance, only when it was able to break out of its isolation and establish links with wider politlce! structures, This study is based on primary sources, interviews and secondary sources. It has engaged archival sources as well as important interviews from both activists and teachers who have taught under both Missionary and Bantu Education.
A Musters thesis s.ibmittcd to the Fllclilly of Education, University of the WHwufcl'sl'and) Johannesburg, in partia! fulfilment of the requirements 1'01' the Degree of Master of Education, DCCCl11bcl' 1995.
Keywords: Students, Black--South Africa--Lebowa--Political activity; Mokopane College (Lebowa, South Africa)